Peran Badan Pusat Statistik dalam Mendukung Literasi Data Dikalangan Mahasiswa - Aminatus Zahriyah; Tia Rahel Amanda; Anis Fitryah; Zuhriyah Zulian Nihrir (Universitas 45 Surabaya, 2025)
In the current era of rapid information development, data literacy has become an essential skill, particularly for students. The Central Statistics Agency (BPS) plays a crucial role in enhancing data literacy among students by providing accurate and relevant statistical data and information. This study aims to explore BPS's contributions to supporting data literacy development in academic environments. Using a descriptive qualitative method, this research collects data through in-depth interviews, participatory observations, and document analysis to understand how students utilize statistical data in their studies. The findings indicate that BPS not only functions as a data provider but also acts as a catalyst for statistical education through various mentoring programs and collaborations with educational institutions. These programs include public lectures, workshops, and the establishment of